Negotiating labour insecurity : a case study of temporary off-farm workers in the deciduous fruit sector in Ceres - Wiltshire, Anne Hilda (Stellenbosch : Stellenbosch University, 2016)
Thesis (MA)--Stellenbosch University, 2016.